Women's perception of sexuality during pregnancy and after birth - Gerda, TRUTNOVSKY; Josef, HAAS; Uwe, LANG; Edgar, PETRU (Australian & New Zealand journal of obstetrics & gynaecology, 2006)
Background:  Pregnancy and birth mark a distinct period in the life of a woman. Hormonal alterations and bodily and social changes impact on women's physical well‐being, mood, relationship and sexuality. Most existing research on sexuality during pregnancy focuses on the quantitative analysis of sexual activities, but neglects subjective experiences of women. Aims:  To examine women's sexual needs, sexual activities, subjective importance of sexuality and contentment with sex life, focusing on the changes over the course of pregnancy and post‐partum. Methods:  Twenty‐six women completed a series of three extensive interviews in early and late pregnancy, as well as 6 months post‐partum. A semiqualitative approach, combining visual analogue scales and a semistructured interview with self‐developed questions, was used. Results:  The statistical analysis revealed a significant decrease of perceived ‘importance of sexuality’, ‘importance of sexual intercourse’ and ‘contentment with present sex life’, from prepregnancy over early pregnancy to late pregnancy, which was followed by a slight increase in the post‐partum period. Samples from the structured interviews provide a detailed insight into female experiences, perceptions and opinions, and demonstrate the high interindividual variability. Conclusion:  Doctors can provide invaluable advice to women regarding the psychosexual changes and help them to understand the normal fluctuations in sexual interest during pregnancy and the post‐partum.